澳門普通小學教師職業幸福感：: 現況、影響因素及提升策略 = THE OCCUPATIONAL WELL-BEING OF MACAU PRIMARY SCHOOL TEACHERS：CURRENT STATUS, INFLUENCING FACTORS, AND ENHANCEMENT STRATEGIES - 黎嘉穎 (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師; 澳門小學; 職業幸福感

As tic na aprendizagem da língua Portuguesa - Simões, Joana Rodrigues (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teacher's Teaching Style and the Learning Attitude of Elementary School Students: A Macau Case Study = 小學生學習態度與教師教學風格現況之研究—以澳門某小學為例 - 洪麗 (University of Saint Joseph, 2024)
Keywords: Learning Attitude; Macau; Primary School; Teacher's Teaching Style; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

探討澳門普通小學教師在融合教育背景下的工作相關壓力及有效應對策略 =: Exploring Work-Related Stress and Effective Coping Strategies in the Context of Inclusive Education Among Mainstream Primary Teachers in Macau - 黃家敏 (University of Saint Joseph, 2024)
Since 2006, the Government of Macau has been promoting inclusive education. This has now been ongoing for seventeen years. As education policies gradually improve, the focus has shifted from students in inclusive settings to the realm of teachers. With an increasing number of inclusive students, the corresponding work pressures faced by teachers has also increased. The aims of this study are to better understand the work-related stress, sources of stress, and subsequent coping strategies used by mainstreamteachers within the inclusive education sector of Macau. This study used qualitative research methods, interviewing twelve frontline teachers from eight different private primary educational institutions. Eight of these teachers work in schools practicing inclusive education, while four were employed in regular schools. However, all twelve participating teachers had experience in teaching inclusive students but also lacked any specialized background in special education. Following and obtaining and meticulously analyzing interview data, supported by relevant literature, the study findings are presented as follows: 1. Views and Attitudes of Regular Teachers in Inclusive Schools towards Inclusive Education The interviewed teachers support the concept of inclusive education but were concerned about student behaviors and their learning challenges. These concerns included inappropriate behaviors, learning disabilities, and the teachers’ own pedagogical demands. In managing student behaviors, teachers found it difficult to handle the emotional control of inclusive students, leading to disruptions in class. Regarding learning, teachers had to use additional and extra time on after-class tutoring, increasing their workload. Teaching inclusive students also complicated the instruction, requiring teachers to undergo additional training and preparation. 2. Work-Related Stress and its Sources among Regular Teachers within Inclusive Schools The participating teachers rated their stress-resilience as not low, but rather they experienced medium to high levels of work-related stress, mainly due to long working hours and extensive workloads. The study identifies four main sources of stress: （i） The nature of work, including extensive teaching and non-teaching tasks, including heavy class management, or multiple roles. （ii） Social relationships, where regular teachers lacked an understanding of resource teachers’ roles, leading to ineffective communication and an underutilization of resource teachers in schools. （iii） Organizational structure, where schools involved in inclusive education required improvements in facilities and teaching environments, particularly in the safety of sports areas. Additionally, not all mainstream teachers had access to inclusive education resources, and the instructional adjustments for inclusive students did not fully meet their needs. （iv） Social aspects, where the public did not fully understand the concepts of inclusive education, and expectations on teachers were excessively high. Furthermore, teachers were dissatisfied with their salaries and benefits, which they felt were not commensurate with their heavy workload. The study also found that female teachers faced additional stress from both work and family responsibilities, as they also bear the burden of caring for and educating their own children at home. 3. Responses and Coping Methods of Regular Teachers in Inclusive Schools to Work-Related Stress The study analyzed the negative impacts of work-related stress on teachers’ physical health, psychological state, and behavior. The impacts included poor sleep quality or insomnia and emotional states of worry and anxiety. In response to stress, teachers engaged in communication and social activities, exercise and rest, and dietary adjustments. However, these stress-relief methods did not effectively address the root causes of the stress, making long-term stress management a crucial issue for teachers. Based on the findings regarding stress perceptions, sources, and coping methods, the researcher proposes recommendations for teachers, educational institutions, and relevant government departments, with an aim to support and aid future policymaking in the area of inclusive education in Macau
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學; 工作壓力; 應對策略; 普通教師; 融合教育

EXPLORING MACAU SECONDARY SCHOOL TEACHERS’ UNDERSTANDING, PROFESSIONAL SKILLS, AND CHALLENGES TO INCLUSIVE EDUCATION OF STUDENTS WITH DISABILITIES/SPECIAL EDUCATION NEEDS - Sin, Sam I. (University of Saint Joseph, 2024)
Quality inclusive education creates educational opportunities for all students to achieve enhanced educational outcomes, and the quality of inclusive teaching depends on teachers’ knowledge, skills, resources and school support. However, not all schools are implementing inclusive education well enough to cater to the learning needs of students with special educational needs. This phenomenological case study explored the perspectives and experiences of five teachers in one inclusive secondary school in Macau. An Interpretative Phenomenological Analysis (IPA) of the in-depth semi- structured interview data revealed four themes: varied conceptualisations of inclusive education, professional training in inclusive practice, professional knowledge and practice experiences, and challenges to implementing inclusive education. Generally, while the teachers demonstrated awareness and some understanding of inclusive education, they also expressed the need for more knowledge and skills to implement inclusive education effectively in their schools. Additionally, they referred to time pressure, workload and insufficient professional development as impeding their personal processes of evolving inclusive teaching in their school. Recommendations were made considering Booth and Ainscow's (2002) Index of Inclusion to enable effective development and practice of inclusive education in the Macau secondary school and extend this to other schools
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; students with special education needs; teachers' professional skills; teachers' understanding

學以致用中文課程（演講）對疑似中文資優學生中文素養提升之研究 ——以澳門某中學高中學生為例 =: A Study On The Improvement Of Chinese Literacy Of Suspected Gifted Chinese Students In The Course Of Learning-to-Use Chinese (Speech) – Taking Senior High School Students Of A Middle School In Macau As An Example - O, Chi Wa (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 中文素養; 學以致用中文課程; 演講; 疑似中文資優; 資優教育

澳門小學普通班教師實施融合教育的教學困擾與因應策略之研究 =: A STUDY ON TEACHING DIFFICULTIES AND RESPONSE STRATEGIES OF TEACHERS IMPLEMENTING INTEGRATED EDUCATION IN ORDINARY CLASSES OF PRIMARY SCHOOLS IN MACAO - Ng, Wa Seng (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 因應策略; 小學普通班教師; 教學策略; 澳門

Sensory play and exploration in early childhood: classroom practices and development - Cardoso, Nair (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學中文科基本學力要求的實施現況研究: 個案研究 - 鄧樂怡 (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring the Problems and Strategy Use by Primary School Teachers in Conducting Classroom Management Under the Policies of Inclusive Education in Macau =: 探討澳門融合教育政策下小學老師面對班級經營的困難及策略 - Lam Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Macau school-based inquiry into shcool :industry links in science - Gull, Nausheen (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Motivation and factors affecting Japanese learning at the institute for tourism studies - Lao, Meng (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The mission, values and the principles of Catholic Schools: the case of Macau from the teachers's perspective - Lemos, Avelino (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Adaptive music composition for ballet fundamental training barre and center practice - Lam, Man Yin (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Exploring the learning effectiveness under the "formative assessment" reform of non-tertiary education in Macao: A Case Study =探討澳門非高等教育改革「形成性評核」下的學習成效－個案研究 - 何愛琴 (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 個案研究; 學習成效; 形成性評核; 教育改革

The effectiveness of active learning for lower motivated students in a Macao school - Ao, Chi Seng (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Moral values in education: a case study of one secondary school in Macau - Chen, Xin Wang (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Curriculum leadership and management - San, Pek Leng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A mathematics curriculum or lower secondary schools in Macau - Wong, Kin Ming (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Effects of students' perception of intelligence on English language learning: a case study in Macau - Dvorska, Jana (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Stress amongst teachers and organizational climate of schools in Macau - Jones, Christon Manuel (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An investigation into students' views of the backwash effects of the English section of the joint admission examination for Macau four higher education institutions (languages and mathematics) - Bramley, Corinna Elaine (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The current situation of Macau secondary multi-media teaching in physics - Ao, Wai Chi (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Realism philosophy and teachers' perceptions of teaching: some implications for school improvement in Macau - Gutierrez, Estrella Cruz (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Community attitudes on disability: an analysis of disability discourse in Macao newspapers - Leong, Weng Ka (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

將CRA教學法融入澳門小學融合班數學課程 之行動研究-以二年級兩位數減法單元為例 =: An Action Study of Integrating Concrete-to-Representational-to-Abstract (CRA) into the Mathematics Learning of Integrated Classes in Macao Primary Schools - Taking the Two-digit Subtraction Unit of Grade 2 as an Example Concrete-to-Representational-to-Abstract (CRA) - Zhuang, YanYan (University of Saint Joseph, 2023)
Keywords: CRA教學策略; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 兩位數减法; 小學數學課程; 融合生; 行動研究

A school-based investigation of school disipline in Macau - Lei, Chi Hang (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Senior secondary students perceptions of virtue and values: a case study in education in Macau - The Reh, Lawrence (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

基模教學對百分比問題之程序流暢程度的有效性研究 =: EFFECTIVENESS OF SCHEMA-BASED INSTRUCTION (SBI) ON PROCEDURAL FLUENCY WITH PERCENTAGES PROBLEMS - Zhou, Mingyan (University of Saint Joseph, 2024)
Research suggested that students struggle because of lacking understanding of basic concepts, formulas, and procedures in algebra, leading to inefficiency in logical thinking and problem-solving skills. (Julius et al., 2018; Jupri et al., 2021). Schemabased instruction (SBI) aims to enhance learning and problem-solving by activating and building upon students' prior knowledge structures, known as schemas (Powell et al., 2008). The common schemas include the total, difference, change, equal groups, comparison, ratios/proportions (Hughes & Cuevas, 2020). SBI has been found to be effective, particularly for students who struggle with mathematics word problems (Marshall, 2012; Hughes & Cuevas, 2020). Research related to SBI has not yet been conducted in Macau region. An early pre-test was administered by the researcher, thirty-one students were asked to solve 10 questions about percentages. The results showed that some students lacked the fundamental knowledge needed to investigate and explore the abstract ideas, patterns, and relationships in percentages problems. A daily schema-based instruction (SBI) as a part of an experimental intervention study was implemented, pre-test and post-tests were administered to investigate the effect of SBI on students' mathematical procedural fluency skills. Thirty-one students from the researcher’s class were invited to engaged in 40 minutes of daily SBI lessons for two weeks, 12 lessons in total. During each of the twelve 40-minute session, students practiced schemas to develop procedural fluency competencies, such as solid number sense and arithmetic operations, to solve percentages problems. Within-group descriptive and inferential statistics were adopted. The results indicated that after SBI, students can solve mathematical problems with greater procedural fluency. This research shares implications and provides suggestions regarding SBI and procedural fluency
Keywords: SBI; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; mathematics; percentages problems; procedural fluency; schema-based instruction; secondary education

Quality assurance for Macao's higher education institutions: challenges and opportunities - Cheong, Wai San (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Walking with John: the go-along as ethnographic tool to explore the lives of adolescents with autism spectrum disorder - Gnanaraj, Steffi (University of Saint Joseph, 2020)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Teachers' perceptions of professional development: a case study of two schools in Macau - Wong, Fong Lei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Inclusive education in Macau: a dual teacher-parent perspective - Lam, Sao Lan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Developing a community-based science curriculum for primary school students in Macau - Ng, Shuk Yan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An interpretative study of three aspects of teacher retention, turnover, and attrition in Macau - Cheong, Ngai Hong (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

An analysis of teacher questions and student responses in a primary school in Macau: a case study - Lee, Soo Mi (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A study of the factors affecting th retention of secondary English teachers in Macao private schools - Tai, Lai Kan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

小學資源教師教學成效及影響因素之研究 =: A STUDY ON THE TEACHING EFFECTS AND INFLUENCING FACTORS OF PRIMARY SCHOOL RESOURCE TEACHERS - Lam, Iok Ian (University of Saint Joseph, 2024)
Keywords: Inclusive Education; Resource Teachers; Teaching Effects; Teaching and Learning Situation; Thesis and Dissertations Master of Education(MED); University of Saint Joseph

Educational leadership practices in East Timor Catholic schools: a case study - Gusmão, Domingos (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A content analysis of views of disability within Portuguese language newspapers in Macau - Amaral, Ana Helena (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Curriculum development of MICE in tertiary education in Macao - Chan, Kam Lun (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

The Collaboration and Challenges Faced by Therapists within Professional Inclusive Education Teams in Macau =: 澳門治療師在融合教育專業團隊中的合作情況及挑戰 - Lao, Pek San (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作模式; 團隊合作; 治療服務; 澳門治療師

Educational technology and the learning of history in a middle school in Macao - Lai, Su Kei (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門普通班教師與資源教師合作教學現況與改進建議之個案研究 =: A CASE STUDY OF CO-TEACHING PRACTICES AND IMPROVEMENT SUGGESTIONS AMONG GENERAL EDUCATION TEACHERS AND RESOURCE TEACHERS IN MACAO - Lai, Chong Weng (University of Saint Joseph, 2023)
Keywords: Inclusive education; Resource teacher; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作教學; 澳門; 融合教育; 資源教師

EXPLORING MUSLIM STUDENTS LIVED EXPERIENCES IN MACAU: A PHENOMENOLOGICAL APPROACH - Ho, Kit Ieng (University of Saint Joseph, 2024)
Muslim community is one of the minority groups in Macau SAR China. Muslims are an interesting group in terms of research because of its diversity in respect to language, nationality, social status, and education level. Groups of people migrate for various reasons such as religion, politics, economy, and education. Individuals experience the age in between nineteen and twenty-four, which fall in the category of youth. Studies of Muslim youths have gained more attention in scholarship, statistical data, and research. The study seeks to understand Muslim students’ life and the needs of this minority group and explores how Muslim students perceive Islam and their own ability to cope with school related cultural pressures through qualitative, phenomenological approach, and focuses on exploring the common experiences of Muslim students in this city. This study used a conceptual framework based on critical race theory (CRT). We use in-depth interviews of five Muslim youth, ages between 19 and 24, to investigate their school life experiences and Islamic practices. We also administered questionnaires and field note to understand their social mobility, social capital and to gain a deeper understanding of their daily lives. A thematic analysis of the interview data produced the following themes: 1) Social mobility; 2) Social capital Relationship with friends; 3) Discrimination and micro-aggressions; and 4) Religion Identity. The study found that the Muslim status of the participants did not have a significant impact on their school experience, as they were able to find accommodation in their practice of religion and school life. However, the multiple identities of the participants as Macau citizens and their ethnic backgrounds did affect their social capital and sense of belonging. The study also examined the experiences of the participants within Macau society, including social factors such as racism. The results indicated that language and ethnicity were factors that hindered their integration into the community. In addition to the original themes, the analysis of the participants' stories in this research revealed two counter-narratives that challenge prevailing narratives. These counter-narratives include the deconstruction of oppressed Muslim women's narratives and the influence of local mainstream religious schooling on Muslim students' religious loyalty. These alternative narratives provide new insights into the lives of Muslim youths and challenge conventional stories. The findings of this study have important implications for educators, academics, and members of both Muslim and non-Muslim communities. By allowing youth to establish broader connections with society and increasing their motivation to participate in and contribute to the community, this study highlights the need for inclusive educational environments that support the diverse identities of students. Furthermore, the study provides young Muslims with a voice in society, empowering them to challenge dominant narratives and promote counter narratives that reflect their experiences and perspectives to meet critical race theory ethos of ongoing active struggle
Keywords: Critical Race Theory; Muslim youth; School experience; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Introducing A Blended Learning Environment to Enhance Student Academic Efficacy - Ho, Io Weng (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Using cooperative learning in an English language classroom - Leong, Cheng In (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

「融合教育下澳門小學普通班教師班級經營面對的困難及可行策略之研究」 =: "A Study on the Difficulties Faced by Macau Primary School General Education Classroom Teachers in Class Management and Possible Strategies" - LEI, WENG KIT (University of Saint Joseph, 2024)
Keywords: Class Management; Inclusive Education; Macau Primary Schools; Qualitative Research; Teacher Attitudes; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師態度; 澳門小學; 班級經營; 融合教育; 質性研究

Challenges in bridging creative education and creative industry - Chan, Kai Pang (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Aprendizagem cooperativa na matemática: uma abordagem de ação-investigação - Alves, Sara Policarpo (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A case study: an analysis of the parental involvement in a Macau secondary school with primary focus on new immigrant parents from Mainland China and Macau local parents - Cheong, Ka Wai (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A process-genre approch in curriculum development for lawyers in Macao: a case study - Fernandes, Raquel de Senna (University of Saint Joseph, 2009)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Challenges and pitfalls of vocational education in Macao: the teachers' voices - Au, Chi Kwun (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A comparative study on the attitudes of Macanese teachers towards inclusive education (IE) from an IE secondary school and a non-IE secondary school - Chan, Chi Seng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

THE LIFE DILEMMA AND ADJUSTMENT OF PARENTS OF CHILDREN WITH AUTISM SPECTRUM DISORDER IN MACAO =: 澳門自閉症類群障礙幼童的家長生活困境與調適 - Ieong, I. Teng (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 困境; 特殊教育; 自閉症兒童家長; 調適

澳門小學非特教專業教師對融合教育之態度研究 =: A study on the Attitudes of the Non-specialized Teachers of Primary Schools in Macau towards Inclusive Education - Ng, Ka Man (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學; 融合教育; 非特教專業教師

小學聽覺障礙學生的融合教育現狀： 以澳門C學校為例 =: CURRENT STATUS OF INTEGRATED EDUCATION FOR STUDENTS WITH HEARING IMPAIRMENT IN PRIMARY SCHOOLS: TAKE MACAU SCHOOL C AS AN EXAMPLE - LIO, I TENG (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 支援服務; 澳門; 聽障學生; 融合教育

澳門教師的情緒智力、幸福感與教學效能之相關研究 =: AN EXPLORATORY STUDY ON THE RELATIONSHIP OF MACAU TEACHERS’ EMOTIONAL INTELLIGENCE, SENSE OF WELL-BEING AND TEACHER SELF-EFFICACY - Wong, Pou I. (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 幸褔感; 情緒智力; 教學效能

澳門高小學生偏差行為現況、成因及處理方法的個案研究 - Wong, Kin Wai (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門教師自我效能感、集體效能感與融合教育態度之相關研究 =: A STUDY ON THE CORRELATION BETWEEN TEACHERS’ SELF-EFFICACY, COLLECTIVE EFFICACY AND ATTITUDES TOWARDS INCLUSIVE EDUCATION IN MACAO - Lei, Man Teng (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師自我效能感; 教師集體效能感; 融合教育態度

澳門私立融合教育學校中資源教師現況與問題之研究 =: A RESEARCH STUDY ON THE CURRENT SITUATION AND FACING PROBLEMS OF RESOURCE TEACHERS IN PRIVATE INCLUSIVE EDUCATION SCHOOLS IN MACAO - Chan, Lok In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門; 私立融合教育學校; 融合教育; 資源教師

澳門融合教育下資源老師心路歷程之質性研究 =: A QUALITATIVE STUDY ON THE SPIRITUAL JOURNEY OF RESOURCE TEACHERS IN INCLUSIVE EDUCATION IN MACAO - Ke, Li Ping (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 心路歷程; 融合教育; 資源老師; 質性研究

Evaluating a Japanese language teaching strategy that comprises a video component - Pun, Oi Ian (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Fashion education and the fashion industry in Macau linked through an NGO - Chan, Victoria Alexa Kuan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Parenting beliefs and practices among Chinese families in Macau: a case study - Ieong, Man Wa (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門小學教師對融合教育態度之研究 =: A Study on Macao Primary School Teachers ’Attitudes towards Inclusive Education - Kwok, Siu Kam (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學教師; 澳門; 融合教育

澳門幼稚園非特教專業教師在融合教育班級經營的困難與應對策略之研究 =: Challenges and Strategies in the Management of Integrated Education Classes: Insights from Non-certified Kindergarten Special Education Teachers in Macau - Leong, Choi Cheng (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門幼稚園; 班級經營; 融合教育; 非特教專業教師

EXPLORING THE RELATIONSHIP BETWEEN WRITTEN COMMUNICATION COMPETENCE AND CULTURAL INTELLIGENCE (CQ): A CASE STUDY OF EFL LEARNERS IN MACAO - Sin, Man Teng (University of Saint Joseph, 2024)
Although Macau students received years of English lectures as compulsory, the outcome could be more favorable when applied to English written performance. In that written communication requires the individual to consider audience perception of the message, a challenge for ESL writers, this study explores whether different forms of feedback can enhance one’s cultural intelligence.The current study looked into the effect of incorporating peer involvement and instructor feedback in written communication, gaining insight into cultural nuances. In order to attain the objective, data were gathered through the utilization of an action research methodology employing a mixed-method design. Grade twelve local students attended a six-week six-week intervention consisting of two cycles. The focus of the intervention nurtured essay writing; the topics of which were inspired by popular musical lyrics, and involved a drafting process that incorporated feedback both from peer editing and the instructor.. The data collected throughout the study involved analysis of written samples (scores of draft and final version) using a paired samples t-test. In addition, students completed a pre-test and post-test survey of the cultural intelligence instrument (CQ), which measured their performance across four domains. There were statistically significant differences between cognitive CQ and motivational CQ between the scores attained before and directly after the intervention.. This study's findings suggest that the written communication of ESL students may be enhanced by adjusting . These findings enriched our understanding of how peer editing and teacher feedback with songs affected the outcomes of second language learners
Keywords: Music; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; cultural intelligence; foreign language anxiety; writing competence

INTEGRATING ROBOTS INTO READING IN AN INCLUSIVE ESL CLASSROOM AT LOWER PRIMARY - Lei, Ut Wa (University of Saint Joseph, 2023)
Establishing and improving the independent reading ability of middle school students has become one of the critical topics in the world, especially for second language learners. The cultivation of independent reading ability has specific challenges. This action research investigated the effectiveness of integrating robot-assisted teaching in reading lessons at lower primary grades. A group of third-grade students (n=15) participated in this research. The instruments include the pre-and post-test of a reading competency test (RCT) and motivational index (MI), a teacher reflection journal, and focus group discussion with parents. The whole intervention is conducted in two cycles, and requires the completion of four 40-minute lessons each week per cycle. The findings support the view that integrating robot-assisted teaching in the classroom can improve students' learning motivation to a certain extent, and that intervention programs positively impact students' learning motivation and independent reading ability in English. This study provides suggestion for the design of English reading instruction, and encourages English teachers to pay more attention to improving students' independent reading ability
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; independent reading skills; learning motivation; robot-assisted teaching

Changing minds: an analysis of the impact of the discovery learning methodologies on the student's attitude towards learning - Churchill, Geoffrey Raymond Alan (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Reading policy and practice: an exploratory case study - Wong, Lai Ha (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門非特教專業小學教師對融合教育態度之研究 - Lei, Oi Meng (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門融合教育小學資源教師的工作困難與需求 =: INCLUSIVE EDUCATION IN MACAO’S PRIMARY SCHOOL：THE WORK DIFFICULTIES AND NEEDS OF PRIMARY RESOURCE TEACHER - Chong, Hei Tong (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學資源教師; 工作困難; 融合教育

探討教師及家長視角下澳門推行生命教育之現況 =: EXPLORING THE CURRENT SITUATION OF LIFE EDUCATION IN MACAU FROM THE PERSPECTIVES OF TEACHERS AND PARENTS - Lei, Choi In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師自我效能; 生命教育; 親社會行為

初任教師在融合教育中教學困擾及因應策略: 以澳門某三所私立學校的初任教師為例 = TEACHING CHALLENGES OF NOVICE TEACHERS AND COPING STRATEGIES IN INCLUSIVE EDUCATION: A STUDY OF NOVICE TEACHERS IN THREE PRIVATE SCHOOLS IN MACAO - Wong, Man U. (University of Saint Joseph, 2024)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 初任教師; 因應策略; 教學困擾; 融合教育

Improving social skills of primary school students through a social skill enhancement program - Fok, Ka Ian (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Gosto de matemática, mas... prefiro estudar direito: compreender a resistência das estudantes às áreas stem - Fernandes, Clara Isabel Raimundo (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

O Jornal Echo Macaense (1893-1899): uma visão da educação em Macau no séc. XIX - Capela, Nuno Gabriel Teixeira (University of Saint Joseph, 2012)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Improvement in English learning by using a systematic learning approach in reading comprehension: a case study in primary school of Macau - Lao, Wai Man (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Parents views of play in Macao infant education - Conceção, Sandra Susana de Matos (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Kindergarten teachers' perception of progressive education: a case study - Leong, Cheng I. (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

澳門幼稚園老師對幼兒偏差行為的態度及輔導策略 - Cheong, Wai Fan (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Music training influences on brain development and as a tool for learning improvement - Ferreira, Ana Filipa Neves (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Content and language integrated learning in higher education: a case study - Santos, Pedro Paulo Pereira Dos (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Diferenças étnico-culturais e expectativas académicas entre dolescentes Macaenses, Portugueses Europeus, Africanos e Chineses ultramarinos: estudo de caso em contexto escolar - Street, Maria Cristina Munhoz (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Trajetórias e identidades profissionais na educação: uma história de vida - Rosa, Sandra Moreira Gaspar (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

EDUCATORS' PERSPECTIVE OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS (SEN) AND THEIR SENSE OF BELONGING, SELF-COMPETENCE, AND AGENCY - Carvalho, Edna Line Henriques de (University of Saint Joseph, 2024)
What strategies did educators use to cultivate a sense of belonging, self-competence, and agency among students with Special Educational Needs (SEN)? Did educators face any challenges in implementing these strategies? Were the findings of this study specific to the inclusive school in Macau, or can they be generalised to other educational settings? This study brings to light educators' inner perspective of students' sense of belonging, self-competence, and agency. Specifically, it aims to uncover the academic and emotional needs of students with SEN and the importance that these may have in promoting a positive educational experience. By gathering the perspectives of educators in an inclusive school in Macau who work side-by-side with these students daily, we can understand how essential these elements are in contributing to their overall development. The purposive sampling approach was used in this study to further investigate various experiences and perspectives of educators within an inclusive classroom setting. The educators interviewed provided insight into an inclusive classroom with students with SEN in full-time attendance. The educators sampled in this study facilitated the search for strategies, challenges and support systems to cultivate a sense of belonging, self-competence and agency, among students with SEN. Findings showed educators' understanding of the importance of students with SEN's sense of belonging, self-competence and agency. The educators' awareness of their students' interactions with peers, and the educators themselves, was prominent, revealing how the sense of belonging for students with SEN affected these relationships. Regarding students' sense of self-competence, according to educators, students with SEN had opportunities to showcase their confidence in specific classroom areas and to exercise independence in the classroom, within the set curriculum and lesson plans. In the findings, educators illuminated the importance of agency in students with SEN. However, they were apprehensive about changes in lesson plans, cultivating a fully independent classroom setting and providing choices to students with and without SEN. The study's implications highlight the educational practices and policies that effectively supplement students with SEN's academic and social environments. The findings of this study aim to guide curriculum developers, educators and parental figures in fostering positive learning experiences for students with diverse learning needs
Keywords: Heutagogy; SEN; Self-competence; Students' agency; Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Percepções de justiça na avaliação de alunos: exploração de situações no ensino secundário em Macau - Pablo, Alberto Manuel da Conceição (University of Saint Joseph, 2011)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Sujeitos ou objecto de aprendizagem? uma experiéncia de aprendizagem cooperativa na catequese da Igreja Católica - Souza, Maria das Virgens Costa de (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Metodologias e estratégias no ensino de vocabulário da língua Portuguesa em duas escolas secundárias de Macau - Rosário, Isabel Dillon Lei Do (University of Saint Joseph, 2015)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

O segredo do sucesso escolar: contributo da web 2.0 - Baptista, Zélia Maria de Oliveira (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

EXPLORING COOPERATIVE LEARNING IN PROMOTING EQUITY, INCLUSION, AND COLLABORATION IN INCLUSIVE CLASSROOMS: A CASE STUDY - Loi, Man Hong (University of Saint Joseph, 2024)
This study presents a case study that explores teachers’ perspectives on the role of cooperative learning as a pedagogical approach in promoting equity, inclusion, and collaboration within inclusive classrooms. Additionally, it identifies both the perceived benefits and challenges associated with its application. The researcher sought data from primary school teachers in one inclusive school in Macau and employed in-depth semi-structured interviews. Twelve participants were involved in this qualitative study. The findings underscore the significant impact of cooperative learning in creating inclusive, engaging, and equitable educational environments, particularly for students with special educational needs. Overall, the participants viewed cooperative learning as a valuable pedagogical approach that fosters equity, interaction, student engagement, and collaboration in inclusive classroom settings. While cooperative learning presents several benefits in promoting an inclusive and equitable learning environment, the findings also reveal unique challenges that require careful management and adaptation by teachers. Some of these challenges include certain students dominating group work, difficulties in integrating students with different disabilities, and time management issues for effective cooperative learning implementation. Overall, the case study contributes valuable insights into to the complex dynamics of cooperative learning in mixed ability classes
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; cooperative learning; inclusion; inclusive education; inclusive practice

Beyond product and into the 21st century: exploring mathematics education in Macau - Marques, Tânia Maria Lemos de Sales (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Improving Students' Reading Literacy with the Guided Use of a Digital Reading Platform in a Chinese Primary School - Norte, Patricia Alexandra D. C. (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Building essential life skills through visual arts in the early years education - Goitia, Isabel Maria Marçal da Silva (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

O impacto das políticas educativas coloniais Portuguesas: o caso de Macau 1835-1920 - Domingues, Maria Alexandra de Aragão Pozal (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Maximizing verbal communication in English amongst Macau Chinese secondary students in private tutorial sessions - Fernandes, Keith Otteran Reis (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Reenquadrar percursos de formação o intérprete-tradutor em Macau: estudo de caso em contexto de trabalho - Costa, Manuela Rosa Franco Serpa Mendes da (University of Saint Joseph, 2014)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Ensino-aprendizagem da matemática: que lugar a mitos? que lugar a Macau? - Oliveira, Maria de Fátima Andrade de (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Biblioteca Escolar como promotora de hábitos de leitura: estudo de caso no primeiro ciclo do ensino básico - Gonçalves, Rosa Maria de Fátima Dias da Silva (University of Saint Joseph, 2013)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Implementation of item response theory to English grammar assessment to map students' understanding and to foster learning - Ho, U. Kei (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph